Two new species of Ceropegia (Apocynaceae, Asclepiadoideae) from eastern Thailand - Kidyoo, Manit (Phytotaxa, 2014)
Two new species from Pha Taem National Park, eastern Thailand, Ceropegia acicularis Kidyoo and C. tenuicaulis Kidyoo (Apocynaceae, Asclepiadoideae), are described, illustrated and compared with the related C. thailandica Meve, from which they differ in growth form, stem branching pattern, type of flower, shape of corolla tube and lobe, and type of hair present on corolla lobe.